A curious menagerie - Berger, Carin (Greenwillow Books, an imprint of HarperCollinsPublishers, 2019)
"Introduces readers to sixty unusual and engaging collective nouns ranging from a flamboyance of flamingos to a mischief of mice. Includes a note about the origin of the collective nouns featured in the book"--